Inclusive Green Growth : The Pathway to Sustainable Development - World Bank (Washington, DC, 2012)
As the global population heads toward 9 billion by 2050, decisions made today will lock countries into growth patterns that may or may not be sustainable in the future. Care must be taken to ensure that cities and roads, factories and farms are designed, managed, and regulated as efficiently as possible to wisely use natural resources while supporting the robust growth developing countries still need. Economic development during the next two decades cannot mirror the previous two: poverty reduction remains urgent but growth and equity can be pursued without relying on policies and practices that foul the air, water, and land.